Predictive value of apparent diffusion coefficient in evaluation of colorectal carcinoma hepatic metastases' response to radiofrequency ablation. Issue 5 (22nd March 2013) - Szurowska, Edyta; Nowicki, Tomasz K.; Izycka‐Swieszewska, Ewa; Zadrozny, Dariusz; Markiet, Karolina; Studniarek, Michal
Abstract : Purpose: To establish the apparent diffusion coefficient (ADC) suitability to evaluate the radiofrequency ablation (RFA) outcome in patients with chemotherapy resistant or partially responding colorectal adenocarcinoma liver metastases. Materials and Methods: A total of 56 patients with 116 metastatic foci over 10 mm in diameter were examined with 1.5 Tesla MRI scanner 1 day before percutaneous RFA treatment. Lesions were evaluated in echo‐planar diffusion‐weighted images with b = 0, 15 and 500 s/mm 2 . On basis of computed tomography scan at 6 weeks, 3 and 6 months after RFA and serum CEA (carcinoembryonic antigen) level lesion were recognized as responding or nonresponding lesions. ADC values for b = 0–15 and 0–500 s/mm 2 of responding and nonresponding lesions were compared. Results: Noncomplete ablation concerned 28 lesions. Mean pretreatment ADC values for b = 0–15 and 0–500 s/mm 2 of responding metastases were significantly lower (2.14 and 1.48 × 10 −3 mm 2 /s) than those of nonresponding tumors (2.7 and 1.74 × 10 −3 mm 2 /s). Sensitivity, specificity, and accuracy of ADC values for b = 0–15 s/mm 2 were 79 (95%CI = 59–92), 85 (95%CI = 76–92), 84%; and for b = 0–500 s/mm 2, the efficacy parameters were, respectively, 78 (95%CI = 56–92), 78 (95%CI = 67–86), and 78%. The P value was under 0.001 for both b parameters. Conclusion: The pretreatment ADCs values of chemotherapy resistant or partially responding colorectal adenocarcinoma liver metastatic lesion can be predictive factor of tumors response to RFA therapy. J. Magn. Reson. Imaging 2013;38:1027–1032. © 2013 Wiley Periodicals, Inc.